Qur’anic Perspectives on Interfaith Marriage: a Comparative Interpretation between Ibn Kathir and al-Munir - Siti Rifatusssaadah Sitorus Pane (Badan Pengelola Masjid Istiqlal, 2024)
This study investigates the complex issue of interfaith marriage through a comparative analysis of two prominent Tafsīr works: Tafsīr Ibn Kathīr and al-Munīr by Wahbah al-Zuḥaylī. Ibn Kathīr’s exegesis adopts a conservative stance, strictly prohibiting marriages between Muslims and non-Muslims, emphasizing the preservation of faith, religious identity, and adherence to traditional legal rulings. In contrast, al-Zuḥaylī’s al-Munīr offers a more contextual and flexible perspective, acknowledging the social realities, pluralistic dynamics, and interreligious interactions characteristic of contemporary societies. Using qualitative content analysis, this study examines the underlying principles, interpretive methodologies, and hermeneutical reasoning employed by each scholar, highlighting the interplay between textual fidelity and contextual considerations. The findings suggest that while Ibn Kathīr prioritizes legal and doctrinal certainty, al-Zuḥaylī emphasizes social cohesion and pragmatic ethics, illustrating how exegetical thought evolves in response to historical, cultural, and societal changes. This comparative framework underscores the importance of fostering dialogue between rigid and contextual interpretations, advocating for approaches that harmonize religious adherence with the principles of tolerance, mutual respect, and coexistence. Beyond legal discourse, interfaith marriage is thus framed as a potential avenue for enhancing interreligious understanding, promoting social integration, and enabling individuals to exercise agency in choosing life partners while navigating the delicate balance between faith and pluralism. This study contributes to ongoing debates in Islamic jurisprudence, modern ethics, and interfaith relations, offering insights for scholars, policymakers, and communities seeking to reconcile tradition with contemporary social realities.